2022
DOI: 10.3389/fceng.2022.823877
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Elimination of Pharmaceutics Found in Water With Hierarchical Silica Monoliths in Continuous Flow

Abstract: Pharmaceutical products (PPs) are considered as emerging micropollutans in wastewaters, river and seawaters, and sediments. The biodegradation of PPs, such as ciprofloxacin, amoxicillin, sulfamethoxazole, and tetracycline by enzymes in aqueous solution was investigated. Laccase from Trametes versicolor was immobilized on silica monoliths with hierarchical meso-/macropores. Different methods of enzyme immobilization were experienced. The most efficient process was the enzyme covalent bonding through glutaraldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…The silica component was then removed by dissolution in a NaOH solution to yield crack-free CM, preserving the same cylindrical shape, diameter, and length as the original silica monoliths. SEM images of CM (Figure ) show that the internal structure has the same homogeneous macropores network as that of the parent silica monolith …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The silica component was then removed by dissolution in a NaOH solution to yield crack-free CM, preserving the same cylindrical shape, diameter, and length as the original silica monoliths. SEM images of CM (Figure ) show that the internal structure has the same homogeneous macropores network as that of the parent silica monolith …”
Section: Resultsmentioning
confidence: 94%
“…Silica monoliths were synthesized as described in our previous work. , Deionized water (24.560 g) was poured into a 100 mL Erlenmeyer flask, and 2.313 g of nitric acid (68%) was added. The mixture was stirred for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“… 1 27 A recent focus is on the immobilization of enzymes for flow-through applications. 8 , 28 31 Conceptually, the methods for enzyme immobilization on silica surfaces can be grouped into at least three categories: (i) covalent binding to a silica surface using organic linker moieties and a chemical modification of the silica surface, 28 , 32 (ii) noncovalent adsorption on either neat silica or surface-modified silica, 27 , 32 and (iii) entrapment in the pores of porous silica materials. 14 , 21 , 32 For the methods based on noncovalent enzyme adsorption, three approaches are relevant for comparison to the work presented: (i) layer-by-layer deposition using a charged polymer that has an opposite charge to the overall charge of the enzyme at the pH applied, 33 , 34 (ii) the use of recombinant enzymes carrying His-tags to bind to a silica surface that is surface-functionalized to allow the efficient binding of His, 24 and (iii) the use of recombinant chimeric enzymes containing a polycationic protein module (an arginine-rich mini protein) that binds to unmodified, anionic silica surfaces (“fusion protein approach”).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, a number of different methods for the immobilization of enzymes on solid surfaces have been developed, as summarized in many review articles. A recent focus is on the immobilization of enzymes for flow-through applications. , Conceptually, the methods for enzyme immobilization on silica surfaces can be grouped into at least three categories: (i) covalent binding to a silica surface using organic linker moieties and a chemical modification of the silica surface, , (ii) noncovalent adsorption on either neat silica or surface-modified silica, , and (iii) entrapment in the pores of porous silica materials. ,, For the methods based on noncovalent enzyme adsorption, three approaches are relevant for comparison to the work presented: (i) layer-by-layer deposition using a charged polymer that has an opposite charge to the overall charge of the enzyme at the pH applied, , (ii) the use of recombinant enzymes carrying His-tags to bind to a silica surface that is surface-functionalized to allow the efficient binding of His, and (iii) the use of recombinant chimeric enzymes containing a polycationic protein module (an arginine-rich mini protein) that binds to unmodified, anionic silica surfaces (“fusion protein approach”). ,, The methodology used in this work is somewhat related to the fusion protein approach, although the use of recombinant enzymes is not required. In our work, the enzyme of interest is immobilized noncovalently on unmodified silica surfaces after several enzyme molecules are first covalently bound to polymer molecules in an aqueous solution. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Barrios-Estrada et al, (2018) found that only 33% of bisphenol-A was degraded in 24 h with an immobilized laccase on the same type of membranes. To overcome some of these disadvantages, meso-/macroporous monoliths have been recently applied for enzyme immobilization, the objective is to provide a big surface area to immobilize a large amount of enzymes, together with a macroporosity which allows low pressure drop while avoiding clogging (Ahmad et al, 2021;Biggelaar et al, 2019;Sebai et al, 2022). Moreover, as far as substrates are forced to flow through the monolith porosity the probability of contact with the biocatalyst is enhanced while allowing a precise control of the contact time (Sanchez Marcano, 2019).…”
Section: Introductionmentioning
confidence: 99%